Puchok travy i jagodka - Andrey Filchenko; L.I.Kalinina; I.K.Mogutaev; Olga Potanina; Julia Kurganskaja (Andrey Filchenko, 2014)
Eastern Khanty, Vasyugan river, text recorded in 1966, by researcher L.I.Kalinina, from speaker Mogutaev I.K. born in 1917 in Ajpolovo village, speaker bi-lingual Khanty-Russian, education - middle school. Archived: Tomsk TSPU Field Archive. Volume Y-5. pp.545-546. Manuscript scanned by Maria Tonojan in 2010; annotated and translated by Andrey Filchenko, Olga Potanina, Julia Kurganskaja, Maria Tonoyan, in 2010. Previously published: (i) in 1976 in cyrillic-based free transcript and Russian free translation, in Kalinina L.I. 1976. Skazki Sibirskogo Severa. V-2. Tomsk. (ii) in 2010 in IPA, morphemic glossing and free translation into Russian and English, in Filchenko A., Potanina O, inter alia. 2012. Annotated folk prose of Ob-Yenissei linguistic area. Tomsk: "Vajar". pp.55-58. Автор текста (рассказчик): Могутаев Иван Кондратьевич. Самоназвание kanty-ku. Родился в 1917 г. в Айполово. Образование 5 классов. Жил в Новом Васюгане. Автор записи (кем записано): Л. И. Калинина: Записано в 1966 г. в п. Н.Васюган, Томская область. Хранится: Архив ЯНС ТГПУ: Том У-5, стр. 507-514. Манускрипт оцифрован каф. ЯНС: - сканирование: Тоноян М.Н., 2010 - набор, глосиирование и перевод: Фильченко А.Ю., Потанина О.С., Курганская Ю.В., Тоноян М.Н., 2010 Ранее опубликован: (1) Калинина Л.И. 1976. Сказки народов Сибирского Севера, вып.II, Томск. (2) Фильченко А., Потанина О., и др. 2012. Аннотированные фольклорные тексты обско-енисейского языкового ареала, Томск: «Вайар». с.55-58. Comprehensive Documentation & Analysis of two Endangered Siberian Languages: legacy data and last speakers of Eastern Khanty and Southern Selkup Eastern Khanty collector of Eastern Khanty narratives and local lore in 1960-1975 speaker of Eastern Khanty, Vasyugan river, recorded in 1966 by L.I.Kalinina